Comprehensive Proteomic Profiling of Urinary Exosomes and Identification of Potential Non-invasive Early Biomarkers of Alzheimer’s Disease in 5XFAD Mouse Model - Song, Zhiqi; Xu, Yanfeng; Zhang, Ling; Zhou, Li; Zhang, Yu; Han, Yunlin; Li, Xianglei; Yu, Pin; Qu, Yajin; Zhao, Wenjie; Qin, Chuan (Frontiers in Genetics, 2020)
ABSTRACT Background: Alzheimer’s disease (AD) is an incurable neurodegenerative disease characterized by irreversible progressive cognitive deficits. Identification of candidate biomarkers, before amyloid-β-plaque deposition occurs, is therefore of great importance for early intervention of AD. Objective: To investigate the potential noninvasive early biomarkers of AD in 5XFAD mouse model, we investigate the proteome of urinary exosomes present in 1-month-old (before amyloid-β accumulation) 5XFAD mouse models and their littermate controls. Another two groups of 2 and 6 months-old urinary samples were collected for monitoring the dynamic change of target proteins during AD progression. Methods: Proteomic, bioinformatics analysis, multiple reaction monitoring (MRM), western blotting (WB) or ELISA were performed for analyzing these urinary exosomes. Results: A total of 316 proteins including 44 brain cell markers were identified using liquid chromatography tandem mass spectrometry. Importantly, eighteen proteins were unique to the 5XFAD group. Eighty-eight proteins including 11 brain cell markers were differentially expressed. Twenty-two proteins were selected to be verified by WB. Furthermore, based on an independent set of 12 urinary exosomes samples, five in these proteins were further confirmed significant difference. Notably, Annexin 2 and Clusterin displayed significant decreased in AD model during the course detected by ELISA. AOAH, Clusterin, and Ly86 are also brain cell markers that were first reported differential expression in urinary exosomes of AD model. Conclusion: Our data demonstrated that some urinary exosome proteins, especially Annexin 2 and Clusterin, as nanometer-sized particles, enable detection of differences before amyloid-β-plaque deposition in 5XFAD mouse model, which may present an ideal non-invasive source of biomarkers for prevention of AD.